The analysis of approaches to the formation of motivation of educational-cognitive activity of students during their basic training - Kolomiiets, A. A.; Kryvoruchko, I. M. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The paper discusses the main approaches to the formation of motivation of educational-cognitive activity, the experi-mental approach of gradual formation of interest of students to the educational-cognitive activity during the study of the fundamental disciplines.